Role of Interleukin-1 family in bone metastasis of prostate cancer - Tong, Yuanhao; Cao, Yinghao; Jin, Tianzhe; Huang, Zhengwei; He, Qinyuan; Mao, Min (Frontiers in Oncology, 2022)
Prostate cancer (PCa) is one of the most fatal diseases in male patients with high bone metastatic potential. Bone metastasis severely shortens overall survival and brings skeletal-related events (SREs) which reduces the life quality of patients, and this situation is currently regarded as irreversible and incurable. The progression and metastasis of PCa are found to be closely associated with inflammatory cytokines and chemokines. As pivotal members of inflammatory cytokines, Interleukin-1 (IL-1) family plays a crucial role in this process. Elevated expression of IL-1 family was detected in PCa patients with bone metastasis, and accumulating evidences proved that IL-1 family could exert vital effects on the progression and bone metastasis of many cancers, while some members have dual effects. In this review, we discuss the role of IL-1 family in the bone metastasis of PCa. Furthermore, we demonstrate that many members of IL-1 family could act as pivotal biomarkers to predict the clinical stage and prognosis of PCa patients. More importantly, we have elucidated the role of IL-1 family in the bone metastasis of PCa, which could provide potential targets for the treatment of PCa bone metastasis and probable directions for future research.